Urban Agriculture in Mogadishu: Opportunities and Constraints - Yasin Mohamed Ibrahim (Turkish Journal of Agriculture: Food Science and Technology)
Urban and peri-urban agriculture is vital for enhancing food security in rapidly growing cities by bridging the food production gap between urban and rural areas. This study employed a snowball sampling technique to gather data from urban farmers in Mogadishu to assess the constraints and opportunities for growing horticultural crops in the city. Utilizing this sampling method, the research identifies key challenges and motivating factors for urban horticulture. Findings indicate that temperature, wind, pest and disease outbreaks, and limited irrigation water significantly restrict production. Farmers using greenhouses experience fewer obstacles due to enhanced protection from environmental factors, improving crop quality. In contrast, those farming in open fields struggle with high irrigation demands, pest infestations, and low-quality yields unattractive to buyers. Leaf miner (Tuta absoluta) and whiteflies are the most prevalent insect populations, sometimes requiring the removal of infested plants to control their spread. The study also observed that urban farmers use two conventional protected farming types, plastic greenhouses and net houses with steel frames, in which plastic greenhouses face issues such as inadequate gutter height and poor ventilation. To combat extreme temperatures, farmers employ primitive methods such as fogging, applying lime solutions, and adjusting greenhouse openings. Additionally, factors like increased market availability, the rise of supermarkets and hotels, rural displacement, diaspora return, and drought-induced vegetable scarcity in rural areas have motivated urban residents in Mogadishu to pursue farming within and around the city.